Effects of the COVID-19 Pandemic on Tdap (Tetanus, Diphtheria, Pertussis) Vaccination During Prenatal Care [A123]. (May 2022) - Smith, Alicia; Paoletti, Andrew; Jaspan, David; Goldberg, Jay
Abstract : INTRODUCTION: It is recommended to administer the tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) vaccine during pregnancy. We evaluated whether the COVID-19 pandemic affected Tdap vaccination during periods when (1) many prenatal visits were via telemedicine and (2) patients might be vaccine wary due to COVID-19 vaccination misinformation. METHODS: This was a retrospective observational study using data queried from the Einstein Healthcare Network electronic medical record. The study included patients who delivered between 2019 and 2021 and their Tdap vaccination status during prenatal care. Chi-square tests compared vaccination rates between patients delivering at different times. RESULTS: Of the pre-pandemic pregnancy control group (n=1, 408), 60% received Tdap vaccination. In the second quarter of 2020, when many prenatal visits were done via telemedicine, patients (n=688) were 1.3 times more likely to not receive Tdap vaccination (54%; P =.0033). During the second quarter of 2021, when there was much misinformation regarding COVID-19 vaccination, even with all prenatal visits being in person, patients (n=363) were 1.3 times more likely to not have received the Tdap vaccination (54%; P =.028). True percentages of Tdap vaccination were higher than those reported above due to 16% of patients who received either prenatal care elsewhere or no prenatal care, for whom no vaccination data was available. CONCLUSION: Compared to pre-COVID-19 pandemic, pregnant patients were less likely (OR, 1.3) to have consented to and received the Tdap vaccination during periods when (1) many prenatal visits were via telemedicine and (2) patients might be vaccine wary due to COVID-19 vaccination misinformation.